CTIM-06. CLINICAL EFFICACY AND BIOMARKER ASSESSMENT OF VT1021, A CD36/CD47 DUAL-TARGETING AGENT, IN RECURRENT GLIOBLASTOMA - Ahluwalia, Manmeet; Battiste, James; Bockorny, Bruno; Bullock, Andrea; Patel, Manish; Wen, Patrick; Shepard, Dale; Vaickus, Lou; Vincent, Melanie; Chen, Jian jenny; Wang, Suming; Watnick, Randolph; et al. (Neuro-oncology (Charlottesville, Va.), 2021)
Glioblastoma (GBM) is the most common and aggressive primary brain malignancy in adults and recurs after treatment in >90% of all patients. Prognosis of patients with recurrent GBM (rGBM) is poor with a median progression free survival of ~1.8 months and median overall survival of 8-10 months. VT1021, a cyclic peptide derived from prosaposin, induces the expression of thrombospondin-1 (TSP-1) in myeloid derived suppressor cells (MDSCs), which are heavily recruited to the tumor microenvironment. Following completion of the Phase 1 Dose Escalation study and determination of the RP2D, an expansion study was conducted in a heavily pretreated rGBM population. The results of the expansion study reveal that VT1021 is safe and well tolerated in rGBM. Pharmacodynamic response to VT1021 was observed by induction of TSP-1 in circulating MDSCs and in the tumor microenvironment. VT1021 demonstrated significant single agent activity. Among 22 evaluable GBM subjects, 3 had complete response (CR), 1 had partial response (PR), and 7 had stable disease (SD) with an average study duration of over 120 days. The overall disease control rate (DCR) was 50%. Among the 3 CR, 2 showed complete radiological regression of the target lesion, the third was found to have no evidence of disease upon pathological examination following surgery. Nine of the 19 (47%) evaluable subjects with available biopsy samples showed high expression levels of both CD36 AND CD47. Among these 9 subjects, 3 achieved CR, representing an overall response rate of 33.3%, with another 3 patients achieving SD for a DCR of 67%. In conclusion, VT1021 demonstrates promising single-agent clinical activity in rGBM, particularly in subjects with high expression levels of CD36 and CD47. Additional clinical studies have been planned to further investigate the efficacy of VT1021 in rGBM and other solid tumor indications.